2021
DOI: 10.1007/s10705-020-10108-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-release N fertilizer to mitigate ammonia volatilization from double-cropping rice

Abstract: Controlled-release nitrogen fertilizer (CRNF) can effectively enhance crop yields and raise the efficiency of nitrogen fertilizer in agroecosystems. In the present study, the volatilization of NH3 was determined by airflow enclosure chamber technique after the application of different CRNF rates in double-cropping rice fields in southern China for continuous 3 years. The early and late season rice (ESR and LSR) were cultivated each year. The results showed that the total NH3 volatilization losses ranged from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Covering the soil surface has many benefits that lead to a noticeable improvement in soil quality and thus increase plant production [12,[46][47][48]. In this study, wheat straw was used as mulch.…”
Section: Discussionmentioning
confidence: 99%
“…Covering the soil surface has many benefits that lead to a noticeable improvement in soil quality and thus increase plant production [12,[46][47][48]. In this study, wheat straw was used as mulch.…”
Section: Discussionmentioning
confidence: 99%
“…Supplying the soil with an adequate amount of nutrients and their uptake by plants is considered proof of the soil capacity and an increase in the use efficiency [50][51][52][53][54][61][62][63][64][65]. The application of BC has many additional benefits for plant nutrient cycling, high retention, leaching reduction, and increased use efficiency, thereby improving soil fertility [35].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, to overcome the above-mentioned challenges, intelligent fertilizers such as slow or controlled release fertilizers that supply active nutrients in a slow manner are being researched into and to a limited scale, they have been produced and used [ 6 ]. Many studies have shown that slow release or controlled released fertilizer (CRF or SRF) can improve the nutrient use efficiency, reduce damage to crop and environment because it is eco-friendly with minimal pollution [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%